Estimating the CDOM absorption coefficient in tropical inland waters using OLI/Landsat-8 images - Alcântara, Enner [UNESP]; Bernardo, Nariane [UNESP]; Watanabe, Fernanda [UNESP]; Rodrigues, Thanan [UNESP]; Rotta, Luiz [UNESP]; Carmo, Alisson [UNESP]; Shimabukuro, Milton [UNESP]; Gonçalves, Stela [UNESP]; Imai, Nilton [UNESP] (Taylor & Francis, 2016)
Coloured dissolved organic matter (CDOM) is the most abundant dissolved organic matter (DOM) in many natural waters and can affect the water quality, such as the light penetration and the thermal properties of water system. So the objective of this letter was to estimate the CDOM absorption coefficient at 440 nm, aCDOM(440), in Barra Bonita Reservoir (São Paulo State, Brazil) using operational land imager (OLI)/Landsat-8 images. For this two field campaigns were conducted in May and October 2014. During the field campaigns remote sensing reflectance (Rrs) were measured using a TriOS hyperspectral radiometer. Water samples were collected and analysed to obtain the aCDOM(440). To predict the aCDOM(440) from Rrs at two key wavelengths (650 and 480 nm) were regressed against laboratory-derived aCDOM(440) values. The validation using in situ data of aCDOM(440) algorithm indicated a goodness of fit, R2 = 0.70, with a root mean square error (RMSE) of 10.65%. The developed algorithm was applied to the OLI/Lansat-8 images. Distribution maps were created with OLI/Landsat-8 images based on the adjusted algorithm.